Crystal structure of hexakis(dimethyl sulfoxide-κO)manganese(II) diiodide - Mathias Glatz; Martina Schroffenegger; Matthias Weil; Karl Kirchner (Acta Crystallographica Section E: Crystallographic Communications, 2016)
The asymmetric unit of the title salt, [Mn(C2H6OS)6]I2, consists of one MnII ion, six O-bound dimethyl sulfoxide (DMSO) ligands and two I− counter-anions. The isolated complex cations have an octahedral configuration and are grouped in hexagonally arranged rows extending parallel to [100]. The two I− anions are located between the rows and are linked to the cations through two weak C—H...I interactions.